(untitled) (Global Journal of Medical Research, 2011)
Mycological and physico-chemical quality of wheaten white bread flour, made for Nigerian market was examined at room temperature of storage for 120days (about four months). During storage, total fungal count was above the maximum acceptable limit of 100 cfu per gram white bread flour. Fungal counts increased towards the end of the storage period but no significant difference of fungal count was noticed during storage. Also slight ecological succession was noticed amongst the various groups of fungi. The fungal isolates from this study were species of Penicillium, Rhizopus, Mucor, Geotricum, Oidium, and Saccharomyces. Three of the four brands of flour analysed had a pH of below 6.0 on the 105 th day of the study. The ash content of the various brands of flour was above 0.65% recommended for flour with effect from day 90 of storage. Protein, gluten, fat, moisture, and carbohydrate contents were within the acceptable limit values for flour. The public health implications of these findings are hereby discussed.